Effect of Twice‐Yearly Denosumab on Prevention of Bone Mineral Density Loss in De Novo Kidney Transplant Recipients: A Randomized Controlled Trial. Issue 6 (29th February 2016) - Bonani, M.; Frey, D.; Brockmann, J.; Fehr, T.; Mueller, T. F.; Saleh, L.; von Eckardstein, A.; Graf, N.; Wüthrich, R. P.
Abstract : We conducted an open‐label, prospective, randomized trial to assess the efficacy and safety of RANKL inhibition with denosumab to prevent the loss of bone mineral density (BMD) in the first year after kidney transplantation. Ninety kidney transplant recipients were randomized 1:1 2 weeks after surgery to receive denosumab (60 mg at baseline and 6 months) or no treatment. After 12 months, total lumbar spine areal BMD (aBMD) increased by 4.6% (95% confidence interval [CI] 3.3–5.9%) in 46 patients in the denosumab group and decreased by −0.5% (95% CI −1.8% to 0.9%) in 44 patients in the control group (between‐group difference 5.1% [95% CI 3.1–7.0%], p   <   0.0001). Denosumab also increased aBMD at the total hip by 1.9% (95% CI, 0.1–3.7%; p   =   0.035) over that in the control group at 12 months. High‐resolution peripheral quantitative computed tomography in a subgroup of 24 patients showed that denosumab increased volumetric BMD at the distal tibia and radius (all p   <   0.05). Biomarkers of bone turnover (C‐terminal telopeptide of type I collagen, procollagen type I N‐terminal propeptide) markedly decreased with denosumab (all p   <   0.0001). Episodes of cystitis and asymptomatic hypocalcemia occurred more often with denosumab, whereas graft function, rate of rejections, and incidence of opportunistic infections were similar. In conclusion, denosumab increased BMD in the first year after kidney transplantation but was associated with more frequent episodes of urinary tract infection. Abstract : This study demonstrates that denosumab, a receptor activator of nuclear factor kB ligand inhibiting monoclonal antibody, effectively increases bone mineral density at vertebral and nonvertebral sites in de novo kidney transplant recipients.